The nature of entrustment : intimacy, exchange, and the sacred in Africa. - Shipton, Parker MacDonald (Yale agrarian studies series., 2007)
This groundbreaking book addresses issues of the keenest interest to anthropologists, specialists on Africa, and those concerned with international aid and development. Drawing on extensive research among Luo people in western Kenya and abroad over many years, Parker Shipton provides an insightful general ethnography. In particular, he focuses closely on nonmonetary forms of exchange and entrustment, moving beyond anthropology's traditional understanding of gifts, loans, and reciprocity. He proposes a new view of the social and symbolic dimensions of economy over the full life course, including transfers between generations. He shows why enduring cultural values and aspirations of East African people, and others around the world, complicate issues of credit, debt, and compensation. The book examines how Luo assess obligations to intimates and strangers, including the dead and the not-yet-born. Borrowing, lending, and serial passing along have ritual, religious, and emotional dimensions no less than economic, Shipton shows, and insight into these connections demands a broad rethinking of all international aid plans and programmes -- Présentation de l'éditeur.